INOVASI KUMBUNG MENGGUNAKAN BEKAS RUMAH UNTUK BUDIDAYA JAMUR TIRAM PADA KELOMPOK WANITA TANI SAIYO JORONG HULU AIA, KECAMATAN HARAU - Suryani, Suryani; Yumarni, Yumarni; Hernawati, Hernawati; Amir, Yusnaweti; Hidayat, Firman; Milantara, Noril; Purnawati, Yuliesi (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Oyster mushroom cultivation has been so widely practiced in Indonesia, both in areas where the climate is cool or rather hot. In general, the kumbung used is made in such a way as to resemble a bamboo hut and usually has a ground floor and a thatched roof. But the cultivation of Oyster mushrooms, which is carried out in the service activities of the Saiyo Jorong Hulu Aia Batu Badukuang Nagari Harau Farmers Group, Harau District, Fifty Cities Regency, uses a former house that is no longer used as an innovation for its kumbung The Women Farmers Group (KWT) is a partner of the Community Service Program by lecturers at the Muhammadiyah University of West Sumatra. The people who have joined have inadequate income. While environmental conditions and cool climates support the cultivation of oyster mushrooms. The method in this service program has 3 stages, namely 1). Socialization, 2) Workshop, 3) Mentoring and 4) Monitoring and Evaluation. This Community Service Program lasts for 8 months, from July 2020 to March 2021. This Community Service Program can improve the economy of the surrounding community. Can increase public knowledge and expertise about oyster mushrooms and mushroom cultivation. Besides that, it can also form a clean environment by using the former house to become a mushroom barn.